A Flexible, Adaptive System for Data-Stream Processing in Energy-Constrained Ad-hoc Networks - Eibel, Christopher; Herbst, Sebastian; Cassens, Björn; Hönig, Timo; Wägemann, Peter; Janker, Heiko; Kapitza, Rüdiger; Meyer-Wegener, Klaus; Schröder-Preikschat, Wolfgang (2016)
Today's generation of sensor networks reflect several changes in system characteristics over traditional sensor networks. These changes affect three key aspects: energy as a fundamental resource, stream data processing, and the inherently dynamic structure of the overall system.   In this paper we extract and present eight distinct challenges aligned to the key aspects which need to be addressed in the future. We use data of ongoing science and research projects to extract the most important challenges. These challenges need to be tackled in order to provide the basis for a flexible and adaptive system design which supports data-stream processing in energy-constrained ad-hoc networks.

Empya: An Energy-Aware Middleware Platform for Dynamic Applications - Eibel, Christopher; Do, Thao-Nguyen; Meißner, Robert; Distler, Tobias (2018)

Empya: Saving Energy in the Face of Varying Workloads - Eibel, Christopher; Do, Thao-Nguyen; Meißner, Robert; Distler, Tobias (Proceedings of the 6th International Conference on Cloud Engineering (IC2E '18), 2018)
UnivIS-Import:2018-02-22:Pub.2018.tech.IMMD.IMMD4.empyas
Keywords: REFIT

Energy-Aware Programming Utilizing the SEEP Framework and Symbolic Execution - Hönig, Timo; Eibel, Christopher; Kapitza, Rüdiger; Schröder-Preikschat, Wolfgang (Proceedings of the 23rd ACM Symposium on Operating Systems Principles (SOSP 2011), Poster Session, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD4.energy

Energy Claims at Scale: Decreasing the Energy Demand of HPC Workloads at OS Level - Eibel, Christopher; Hönig, Timo; Schröder-Preikschat, Wolfgang (Proceedings of the 12th IEEE Workshop on High-Performance Power-Aware Computing (HPPAC), 2016)
UnivIS-Import:2016-06-01:Pub.2016.tech.IMMD.IMMD4.energy
Keywords: Energy Awareness; Operating-System Support; High-Performance Computing

From Radio Telemetry to Ultra-Low Power Sensor Networks - Tracking Bats in the Wild - Dressler, Falko; Ripperger, Simon; Hierold, Martin; Nowak, Thorsten; Eibel, Christopher; Cassens, Björn; Mayer, Frieder; Meyer-Wegener, Klaus; Kölpin, Alexander (IEEE Communications Magazine, 2016)
Sensor networks have successfully been used for wildlife monitoring and tracking of different species. When it comes to small animals such as smaller birds, mammals, or even insects, the current approach is to use extremely lightweight RF tags located using radio telemetry. A new quantum leap in technology is needed to overcome this limitation and enable new ways to observe larger numbers of small animals. In an interdisciplinary team, we are working on the different aspects of such a new technology. In particular, we report on our findings on a sensor-network-based tracking solution for bats. Our system is based on integrated localization and wireless communication protocols for ultra-low-power systems. This requires coding techniques for improved reliability as well as ranging solutions for tracking hunting bats. We address the technological and methodical problems related to system design, software support, and protocol design. First field experiments have been conducted that showcase the capabilities of our system.
UnivIS-Import:2015-10-26:Pub.2015.tech.IMMD.IMMD4.fromra

Monitoring Bats in the Wild: On Using Erasure Codes for Energy-Efficient Wireless Sensor Networks - Dressler, Falko; Mutschlechner, Margit; Li, Bijun; Kapitza, Rüdiger; Ripperger, Simon; Eibel, Christopher; Herzog, Benedict; Hönig, Timo; Schröder-Preikschat, Wolfgang (ACM Transactions on Sensor Networks, 2016)
UnivIS-Import:2016-06-01:Pub.2016.tech.IMMD.IMMD4.monito
Keywords: Algorithms; C.2.2 [Computer-Communication Networks]: network Protocols; Design; Energy efficiency; Erasure codes; Forward error correction; Performance; Reliable communication; Wireless sensor networks

Playing Hare and Tortoise: The FigarOS Kernel for Fine-Grained System-Level Energy Optimizations - Hönig, Timo; Eibel, Christopher; Herzog, Benedict; Janker, Heiko; Wägemann, Peter; Schröder-Preikschat, Wolfgang (Proceedings of the 2015 Brazilian Symposium on Computing Systems Engineering (SBESC '15), 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.IMMD.IMMD4.playin
Keywords: PAX; COKE; InvasIC

Proactive Energy-Aware Programming with PEEK - Hönig, Timo; Janker, Heiko; Mihelic, Oliver; Eibel, Christopher; Kapitza, Rüdiger; Schröder-Preikschat, Wolfgang (Proceedings of the 2014 Conference on Timely Results in Operating Systems (TRIOS '14), 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD4.proact

Proactive Energy-Aware System Software Design with SEEP - Hönig, Timo; Eibel, Christopher; Schröder-Preikschat, Wolfgang; Kapitza, Rüdiger; et al. (Proceedings of the 2nd Workshop on Energy Aware Software-Engineering and Development, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD4.proact

SEEP: Exploiting Symbolic Execution for Energy-Aware Programming - Hönig, Timo; Eibel, Christopher; Kapitza, Rüdiger; Schröder-Preikschat, Wolfgang (Proceedings of the 4th Workshop on Power-Aware Computing and Systems (HotPower 2011), 2011)
In recent years, there has been a rapid evolution of energy-aware computing systems (e.g., mobile devices, wireless sensor nodes), as still rising system complexity and increasing user demands make energy a permanently scarce resource. While static and dynamic optimizations for energy-aware execution have been massively explored, writing energy-efficient programs in the first place has only received limited attention. This paper proposes SEEP, a framework which exploits symbolic execution and platform-specific energy profiles to provide the basis for energy-aware programming. More specifically, the framework provides developers with information about the energy demand of their code at hand, even for the invocation of library functions and in settings with multiple possibly strongly heterogeneous target platforms. This equips developers with the necessary knowledge to take energy demand into account during the task of writing programs. © 2011 ACM.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD4.seepex

SEEP: Exploiting Symbolic Execution for Energy-Aware Programming - Hönig, Timo; Eibel, Christopher; Kapitza, Rüdiger; Schröder-Preikschat, Wolfgang (Best Papers from SOSP 2011 Workshops, 2012)
UnivIS-Import:2015-04-20:Pub.2012.tech.IMMD.IMMD4.seepex

Strome: Energy-Aware Data-Stream Processing - Eibel, Christopher; Gulden, Christian; Schröder-Preikschat, Wolfgang; Distler, Tobias (Proceedings of the 18th International Conference on Distributed Applications and Interoperable Systems (DAIS '18), 2018)
Handling workloads generated by a large number of users, data-stream–processing systems also require large amounts of energy. To reduce their energy footprint, such systems typically rely on the operating systems of their servers to adjust processor speeds depending on the current workload by performing dynamic voltage and frequency scaling (DVFS). In this paper, we show that, although effective, this approach still leaves room for significant energy savings due to DVFS making conservative assumptions regarding its impact on application performance. To leverage the unused potential we present Strome, an energy-aware technique to minimize energy demand in data-stream–processing systems by dynamically adapting upper limits for the power demand of hardware components. In contrast to DVFS, Strome exploits information on application performance and is therefore able to achieve energy savings while minimizing its effects on throughput and latency. Our evaluation shows that Strome is particularly effective in the face of varying workloads, reducing power demand by up to 25 % compared with the state-of-the-art data-stream–processing system Heron relying on DVFS.<br

Towards Energy-Proportional State-Machine Replication - Eibel, Christopher; Distler, Tobias (Proceedings of the 14th Workshop on Adaptive and Reflective Middleware (ARM '15), 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.IMMD.IMMD4.toward_6
Keywords: REFIT

What does Power Consumption Behavior of HPC Jobs Reveal?: Demystifying, Quantifying, and Predicting Power Consumption Characteristics - Patel, Tirthak; Wagenhäuser, Adam; Eibel, Christopher; Hönig, Timo; Zeiser, Thomas; Tiwari, Devesh (Proceedings - 2020 IEEE 34th International Parallel and Distributed Processing Symposium, IPDPS 2020, 2020)
As we approach exascale computing, large-scale HPC systems are becoming increasingly power-constrained, requiring them to run HPC workloads in an energy-efficient manner. The first step toward achieving this goal is to better understand, analyze, and quantify the power consumption characteristics of HPC jobs. However, there is a lack of understanding of the power consumption characteristics of HPC jobs which run on production HPC systems. Such characterization is required to guide the design of the next generation of power-aware resource management. To the best of our knowledge, we are the first study to open-source the data and analysis of power-consumption characteristics of HPC jobs and users from two medium-scale production HPC clusters.
Created from Fastlane, Scopus look-up